PENGARUH PEMBERIAN MADU TJ TERHADAP KENAIKAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI PUSKESMAS TIOM - Wahyuni, Sri; Iriyani, Nur Fitriana; Towolom, Ilitara W (NHM PRESS, 2023)
As many as 20.3% of pregnant women experience anemia in the Lanny Jaya Health Office area. In general, honey is efficacious for producing energy, increasing endurance, and increasing stamina. Honey contains magnesium and iron. The aim of the study was to determine the effect of TJ honey on increasing Hb levels in pregnant women at the Tiom Health Center. This type of research is a quasi-experimental method (Quasi Experiment) using One Group Pre Test and Post Test Design. The research was conducted in February-March 2023. The sampling technique used was purposive sampling with a total sample of 30. The measuring tool or instrument used was the Hb Quick Check tool. The test results using the Paired T Test in this study obtained a p value of 0.000 (<0.05), which means that there was an effect of giving TJ honey on increasing Hb levels in pregnant women. There was an increase in Hb levels before being given TJ honey, a mean value of 9,307 was obtained and after being given TJ honey for 14 days, a mean value was obtained of 11,657. Suggestions for pregnant women to consume TJ honey at least 1 spoon every day in addition to taking blood supplement tablets given by the Health Center in order to further increase Hb levels in pregnant women.